Analysis of the Icelandic fishing industry as a system - Árni Stefán Haldorsen 1989- (2017)
The fishing industry is one of the cornerstones of the Icelandic economy, as well as being deeply embedded in the nation’s culture. With modern fishing techniques, the strain on the fish biostocks has increased significantly, and protecting the resource has become a matter of great importance. A good understanding of the resource is vital, as is understanding the system by which the resource is harvested, processed and sold. The mapping of the Icelandic fishing industry from a system’s perspective could provide valuable insight for a responsible use of the resource by examining the system in a holistic way. Using the methods of systems analysis, the Icelandic fishing industry was mapped using stock-and-flow diagrams (SFDs) and causal-loop-diagrams (CLDs). The system was examined on a macro scale, focusing on the flow of fish from the oceans to the consumers and the opposite flow of currency. Key feedback loops were identified from the CLDs. A simplified version of the diagrams was made, from which a computer model was generated using the STELLA software and simulations done for the Atlantic cod (Gadus morhua). The simulations were able to recreate the system's behavior to an acceptable level and the results show that the current use of the resource is within the parameters of sustainability, while yielding a good economic growth.